2020
DOI: 10.1002/pon.5610
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of body image in adolescents and young adults (AYAs) with cancer

Abstract: Context Among adolescents and young adults (AYAs), cancer and its treatment can disturb body image in distinct ways compared to younger or older individuals. Objective Since AYA body image is not well understood, this study was designed to develop a conceptual framework for body image in AYAs with cancer. Methods Concept elicitation interviews were conducted with 36 AYA patients [10 adolescents (15–17 years), 12 emerging adults (18–25 years), 14 young adults (26–39 years)] and health care providers (n = 36). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Different studies have supported the need of understanding the complexity of body image within the AYA population [ 4 , 11 , 13 , 21 ]. A recent scoping review by Vani et al [ 13 ] showed that existing quantitative studies are mainly addressing body image from the perspective of tumor histology, focusing on specific cancer groups, rather than from an AYA-specific perspective [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have supported the need of understanding the complexity of body image within the AYA population [ 4 , 11 , 13 , 21 ]. A recent scoping review by Vani et al [ 13 ] showed that existing quantitative studies are mainly addressing body image from the perspective of tumor histology, focusing on specific cancer groups, rather than from an AYA-specific perspective [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review by Vani et al [ 13 ] showed that existing quantitative studies are mainly addressing body image from the perspective of tumor histology, focusing on specific cancer groups, rather than from an AYA-specific perspective [ 13 , 14 ]. The available studies with an age-specific focus have a qualitative design, indicating that currently little is known about the prevalence and what factors are associated with a negative body image [ 21 , 22 , 23 , 24 ]. Moreover, despite the possible long-term effects of cancer on body image, within the AYA literature limited attention has been given to long-term AYA cancer survivors (>five years after diagnosis) [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multinomial logistic regression revealed that the unmet daily life needs, e.g., the ability to cope with physical and appearance changes and the ability to manage medication and side effects, were significantly associated with lower odds of reporting good or very good/excellent health versus fair or poor health, suggesting these needs negatively impact AYA cancer survivors’ general health. [ 32 ] Many AYAs, for example, report cancer-related post-treatment fatigue as one of the most prevalent and severe symptoms they experience, and cancer-related fatigues are persistently disruptive to their sleep quality and motivation. [ 33 ] Similarly, Brock and colleagues (2022) found that achieving maximum work ability is a major challenge for AYAs, and many reported compromised cognitive capacity (e.g., poor concentration or low attention span) for work.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because infertility ties into YA body image as well as their sense of self-worth, another study highlighted the psychological impact of fertility on body image by demonstrating that up to 25% of YA pursued fertility preservation before their cancer treatment 21. Moreover, previous studies have shown that changes in physical appearance can increase emotional distress, reduce quality of life, and contribute to social isolation and feeling different from their peers without cancer 22–24. These changes include new stomas, prosthetics, hair loss, and surgical scars.…”
Section: Discussionmentioning
confidence: 99%